Effects of cadmium on gas exchange and phytohormone contents in citrus - Lopez-Climent, M.F.,Univesidad Jaume I, Castellon (Spain). Dept. de Ciencias Agrarias y del Medio Natural; Arbona, V.,Univesidad Jaume I, Castellon (Spain). Dept. de Ciencias Agrarias y del Medio Natural; Perez-Clemente, R.M.,Univesidad Jaume I, Castellon (Spain). Dept. de Ciencias Agrarias y del Medio Natural; Gomez-Cadenas, A.,Univesidad Jaume I, Castellon (Spain). Dept. de Ciencias Agrarias y del Medio Natural (Biologia plantarum, 2011)
The effect of increased Cd2+ concentrations in the watering solution on citrus physiology was studied by using two citrus genotypes, Cleopatra mandarin and Carrizo citrange. Cd content in roots and leaves was tested together with measurements of leaf damage, gas exchange parameters, and hormonal contents. Citrus roots efficiently retained Cd2+ avoiding its translocation to the shoots and Cleopatra mandarin translocated less Cd2+ than Carrizo. With increasing Cd2+ concentration all gas exchange parameters were decreased more in Carrizo than in Cleopatra mandarin. Cd-induced increases in abscisic acid and salicylic acid contents were observed in leaves but not in roots of the studied genotypes.